Application of data mining on inventory grouping using clustering method - Ramadani, Suci; Hidayat, Syukri; Ramahdanty, Ramahdanty (Jurnal Teknik Informatika C.I.T Medicom, 2023)
Data mining in the business field is considered important, because the inventory system of goods in a store and what types of goods are the top priorities that must be stocked to anticipate the vacancy of goods, so that the store owner can find out the most sold items and the lack of stock items. The existence of daily sales transaction activities at Sahabat Komputer stores will produce a pile of data that is getting bigger and bigger, so that it can cause new problems. If this is allowed, the transaction data will become a pile of data that is detrimental because it requires an increasingly large storage media or database. One way to overcome this is to keep the availability of various types of continuous goods in the warehouse. To find out what items are purchased by consumers, the technique of analyzing the inventory of goods in the warehouse is carried out. Application of Clustering, helps in grouping data of the same characteristics into the same region. And from the whole it can be concluded that in cluster 1 the stock is available on average 1-100 pcs, the number of sales is 1-100 pcs and the sales volume per month is 1-100 units. In cluster 2 there is an average available stock of 101-200 pcs, 101-200 pcs sales quantity of 101-200 units, and monthly sales volume of 101-200 pcs. And in cluster 3 there is an average available stock of 301-400 pcs, the number sold is 401-500 pcs, and the monthly sales volume reaches 301-400 pcs.